THE INFLUENCE OF COMPETENCY ON EMPLOYEE PERFORMANCE: (A LITERATURE REVIEW) - Fatmasari Wijayanti; Retno Titi Sari (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
This article aims to elaborate our literature review regarding competency, employee performance, as well as the relation between competency and employee performance. We use literature review method to understand this relationship between both of them. We are not only describing the facts from the literature review, but also providing adequate understanding and explanation. The results of several previous theories and researches indicate that employee competency has an influence on employee performance. The results of these studies could be empirical evidences that organizations require employees who have a great competency at work. Organizations need competent employees to be able to overcome the challenges and the changes in their environment. Employees who have competency will be relatively easier to do their work and to evolve because basically they already have good skills to complete assigned tasks effectively, efficiently and competitively. Accordingly, organizations need to concern and improve employee competency. This can be done by competency mapping through training which is suitable with the job requirements thus employees have updated competency that are relevant to the job and the changes in the organization's environment. Competency mapping could increase employee productivity and employee performance as well as organization's efficiency, effectiveness and competitiveness as a whole.